Determinação de metais na água, sedimento e em moluscos bivalves do complexo estuarino de Paranaguá, Paraná, Brasil - Oliveira, Ana Paula Franco de (2019)
Estuaries are unique environments with high biological productivity, and favor human occupation and economic activities, which results in anthropic pressures. The Paranaguá Estuary Complex suffers from the actions generated by the industrial and port activities resulting from the development. To assess the integrity of an ecosystem, it is important to analyze physical, chemical, and biological parameters. Bivalves are considered appropriate organisms in biomonitoring studies to be benthic and indicate environmental change. In addition, those organisms are an important source of food and income for the local population. This study aims to determine the concentration of metals in water, sediment and bivalve molluscs Anomalocardia brasiliana and Mytella guyanensis, and to obtain data related to environmental characteristics in order to relate to the population dynamics of molluscs. The samples were carried out at different seasonal periods, in five points. The biometric variables of the bivalves were obtained, the nutrient analyzes in the water were carried out as well as the metal contents in the water, the sediment and the molluscs. Data were assessed for normality using the Shapiro-Wilk test. The Kruskal-Wallis variance test was used to indicate if there were significant differences between seasonalities. For correlation analysis it was used the Spearman test. During the sampling period, it was observed a variation in the length of Mytella guyanensis individuals from 13.54 to 50.90 mm and from 4.01 to 30.78 mm for Anomalocardia brasiliana individuals. The growth of A. brasiliana showed significant positive correlations with phosphorus and ammoniacal nitrogen concentrations. The growth of M. guyanensis did not present significant correlations with the nutrients. The analysis of metals in water and sediment showed high concentration of aluminum and iron, and specific concentration of lead, chromium, nickel, zinc and copper. Values of iron, aluminum, nickel and chromium were found in the organisms. The main correlations found between bivalve growth and metal concentrations were iron and aluminum elements due to their availability in the environment, but it is also identified significant correlations for chromium and nickel. The results demonstrate that the species A. brasiliana and M. guyanensis are able to reflect the degree of environmental contamination and can be used as biomarkers.